HUBUNGAN KADAR UREUM DAN KREATININ SERUM DENGAN FUNGSI KOGNITIF PENDERITA PENYAKIT GINJAL KRONIK - Adzra Fadhila Iswan; Restu Susanti; Dian Pertiwi; Lydia Susanti; Almurdi Almurdi; Miftah Irramah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Chronic Kidney Disease (CKD) may lead to various complications, including cognitive impairment. The causative factor is the toxic substances accumulation in the body, including serum ureum and creatinine. This study aimed to determine the relationship between serum ureum and creatinine levels with cognitive function in CKD patients. Samples were taken using a consecutive sampling technique on 46 CKD patients who were hemodialyzed at RSUP Dr. M. Djamil Padang. Cognitive function was assessed using the Montreal Cognitive Assessment Indonesian version (MoCA-Ina). Serum ureum and creatinine were measured with a spectrophotometer. Data were analyzed using the Chi-Square test. Results showed that CKD patients with cognitive impairment were more likely to be older than 50 years old (54.2%) and male (58.3%), had at least a high school education and above (70.8%), were accompanied by hypertension (75%), and without diabetes mellitus (91.7%). The median serum ureum and creatinine levels in patients with cognitive impairment were 124 mg/dL and 10.05 mg/dL. The relationship between serum ureum and creatinine levels with cognitive function had a 0.039 and 0.768 p-value. There is no relationship between the characteristics of the sample, including age, gender, education level, hypertension, and diabetes mellitus with cognitive function in CKD patients. There is a significant relationship between serum ureum levels and cognitive function, but a non-significant relationship between serum creatinine with the cognitive function of CKD patients.